ETHICAL DILEMMAS IN THE CHURCH’S PASTORAL MINISTRY REGARDING THE PRACTICE OF COHABITATION WITHOUT FORMAL MARRIAGE - Brayen Josua Nggariwo (Diegesis : Jurnal Teologi, 2026)
This study examines the ethical dilemma in church pastoral ministry toward cohabitation without formal marriage, highlighting the gap between the normative affirmation of marriage as a covenant and the need for contextual pastoral accompaniment. Previous studies have tended to assess cohabitation from moral or sociological perspectives but have not articulated an integrative pastoral response model. This qualitative case study involved purposively selected participants (pastors, church elders, and cohabiting couples). Data were collected through semi-structured interviews, limited observation, and literature review, and analyzed using thematic coding. An Aristotelian virtue ethics framework was synthetically integrated with Franz Magnis-Suseno’s ethics of responsibility and enriched by a deontological perspective from Immanuel Kant, particularly concerning moral duty and the categorical imperative as a universal norm. This deontological lens sharpens the analysis of moral obligation, public commitment, and respect for human dignity within relational structures. Findings indicate that cohabitation is primarily driven by economic pressures and customary demands rather than theological rejection, and that churches adopt a moderative strategy: liturgical inclusion combined with structural restrictions. The study contributes to the formulation of a gradual pastoral model that upholds doctrinal integrity while fostering relational transformation.